1989
DOI: 10.1128/mcb.9.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical characterization of the human trk proto-oncogene.

Abstract: Molecular analysis of the human irk oncogene, a transforming gene isolated from a colon carcinoma biopsy, revealed the existence of a novel member of the tyrosine kinase gene family. This locus, which we now designate the trk proto-oncogene, codes for a protein of 790 amino acid residues that has several features characteristic of cell surface receptors. They include (i) a 32-amino-acid-long putative signal peptide, (ii) an amino-terminal moiety (residues 33 to 407) rich in consensus sites for N-glycosylation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
396
0
4

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 578 publications
(408 citation statements)
references
References 52 publications
8
396
0
4
Order By: Relevance
“…The human TrkA cDNA was stably expressed in Rat1MycER TM cells using the expression vector pMEX-neo (Martin-Zanca et al, 1989). Expression of the 140 and 110 kDa TrkA proteins was monitored by immunoprecipitation with the TrkA-speci®c monoclonal antibody MGR12 (Cabrera et al, 1996) followed by Western blot analysis using a pan-Trk antibody (anti-203;Martin-Zanca et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human TrkA cDNA was stably expressed in Rat1MycER TM cells using the expression vector pMEX-neo (Martin-Zanca et al, 1989). Expression of the 140 and 110 kDa TrkA proteins was monitored by immunoprecipitation with the TrkA-speci®c monoclonal antibody MGR12 (Cabrera et al, 1996) followed by Western blot analysis using a pan-Trk antibody (anti-203;Martin-Zanca et al, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…cDNAs encoding the full length wt-TrkA receptor, or the single-site mutants (Y490F, Y785F) were expressed using the pMEX-neo expression vector (Martin-Zanca et al, 1989). The kinase-inactive mutant (K538A) was expressed from a pCMV5-based expression vector (a gift from Dr Moses Chao, Cornell University, NY), and the double mutant (Y490/785F) from a pLNCX-5-derived expression vector (a gift from Dr David Kaplan, McGill University, Montreal).…”
Section: Generation Of Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat TrkA [22] and rat TrkB [23] sequences correspond to the ones of the L2A and L2B peptides used in this work. The sequences of human TrkA, mouse TrkB, and chick TrkB were taken from Martin-Zanca et al [19], Klein et al [12], and Dechant et al [3], respectively. The localizations of the motifs within the respective proteins are indicated by the numbers on either side of the sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that expression of TrkA, TrkB or TrkC in NIH3T3 ®broblasts induces a potent mitogenic response when stimulated with their respective ligands (Cordon-Cardo et al, 1991; Glass et al, 1991;Lambelle et al, 1991). Indeed, TrkA was originally identi®ed as an oncogenic protein that led to the ligand-independent transformation of NIH3T3 cells (Martin-Zanca et al, 1989).…”
Section: Bdnf-inducible Viability and Proliferation Of Trkb-3t3 Cellsmentioning
confidence: 99%